Intermittency in Transitional Shear Flows - Duguet, Yohann (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book contains original peer-reviewed articles written by some of the most prominent international physicists active in the field of hydrodynamics. The topic is entirely devoted to the study of the transitional regimes of incompressible viscous flow found at the onset of turbulent flows. Nine articles written for this 2020 Special Issue of the journal Entropy (MDPI) have been gathered at the crossroads of fluid mechanics, statistical physics, complexity theory, and applied mathematics. They include experimental, analytic, and computational material of an academic level that has not been published anywhere else.